Anticarcinogenic and antioxidant activity of diindolylmethane derivatives - BENABADJI Sakina Hayat; WEN Ren; ZHENG Jian-bin; DONG Xiao-chun; YUAN Shen-gang (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the synthesis methods and the bioactivity of diindolylmethane (DIM) derivatives. METHODS: 1) A 3D-Quantitative Structure-Active Relationships (QSAR) Comparative Molecular Field Analysis (CoMFA) study of 14 DIM derivatives was investigated to predict their anticarcinogenic activity. 2) Based on CoMFA model, a series of new derivatives of DIM were designed and synthesized. 3) Their free radical scavenging and antioxidant potentials were tested using in-vitro DPPH radical scavenging and ?-carotene antioxidant models. 4) The anticarcinogenic activities of some compounds were tested by using microculture tetrazolium assay (MTT) and sulforhodamine B (SRB) proteochromosomic assays. RESULTS: 1) The CoMFA model derived from DIM analogues proved a good predictive ability with q2 value of 0.827. 2) New designed compounds 3c and 4c exhibited 3-fold more potent radical scavenging activity than reference substance Vitamin E in DPPH model expressed by IC50 values. 3) The primary antitumor screening essay showed that some DIM derivatives designed exhibited the inhibitory activities to some tumor cell growth at relatively high concentration, and DIM was the most effective among them. CONCLUSION: DIM's 3D-QSAR model is reliable. According to it, eleven DIM derivatives were synthesized, and two derivatives of them possess potent radical scavenging activities and some showed the inhibitory activities in primary anticancer assay in vitro.